Chisomicines D and E, Two New Limonoids from Chisocheton ceramicus - Ibrahim A. Najmuldeen; A. Hamid A. Hadi; Khalit Mohamad; Khalijah Awang; Kamal Aziz Ketuly; Mat Ropi Mukhtar; Hairin Taha; Noraziah Nordin; Marc Litaudon; Françoise Guéritte; Alfarius Eko Nugroho; Hiroshi Morita (The Japan Institute of Heterocyclic Chemistry, 2024)
Volume: 84 No: 2